2006
DOI: 10.1159/000106787
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 Expression Is an Independent Unfavorable Prognostic Factor in Esophageal Squamous Cell Carcinoma

Abstract: Objective: ATP-binding cassette, subfamily G, member 2 (ABCG2) is a new member of the superfamily of ATP-binding cassette transporter proteins and known to be not only a member of the membrane transporters implicated in multidrug resistance, but also a molecular determinant of the side population phenotype, characteristics of which are reminiscent of stem cells. The aim of the current study was to clarify the significance of ABCG2 expression in esophageal squamous cell carcinoma (ESCC). Methods: We immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…A significant correlation was found between ABCG2 expression and clinical stage and lymph node metastasis. In accordance with research in acute myeloid leukemia (11,27,28), adult acute lymphoblastic leukemia (29), non-small cell lung cancer (15) and esophageal squamous cell carcinoma (14), positive expression of ABCG2 may accelerate progression and metastasis in HNSCC. However, no significant correlation, only an increasing trend between ABCG2 expression and histological grade, was observed in the tumor tissues of the laryngeal and nasopharyngeal cancers.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A significant correlation was found between ABCG2 expression and clinical stage and lymph node metastasis. In accordance with research in acute myeloid leukemia (11,27,28), adult acute lymphoblastic leukemia (29), non-small cell lung cancer (15) and esophageal squamous cell carcinoma (14), positive expression of ABCG2 may accelerate progression and metastasis in HNSCC. However, no significant correlation, only an increasing trend between ABCG2 expression and histological grade, was observed in the tumor tissues of the laryngeal and nasopharyngeal cancers.…”
Section: Discussionsupporting
confidence: 67%
“…ABCG2 overexpression has been observed in many cell lines and tumor types (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), where it functions to pump a wide variety of endogenous and exogenous compounds out of cells (17)(18)(19)(20)(21). ABCG2 was demonstrated to be associated with cancer stem cells and multidrug resistance (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…11 These in vitro studies have correlates in the clinical setting, where the expression and activity of ABCG2 has been linked to radiotherapy resistance. 12 Interestingly, several studies suggest that ABCG2 may also be an indicator of poor prognosis in some tumors, including lung, 36 breast, 37 and esophageal cancers 38 even in the absence of drug treatment. Together, these observations suggest a role for ABCG2 in general tumor cell survival independent of its well-characterized drug efflux function.…”
Section: Discussionmentioning
confidence: 99%
“…CSCs display greater resistance to radioand chemotherapy compared with more differentiated tumor cells, which indicates that the CSC subset can escape from conventional cancer therapy to initiate and perpetuate tumorigenesis (35). In multiple independent studies, the CSC population has been associated with poor patient prognosis in ESCC, which is the sixth leading cause of cancer deaths worldwide (28,36,37). Huang and colleagues reported that the CSC population in ESCC displays robust resistance to radio-and chemotherapy (38) and correlates with the risk of mortality in this disease.…”
Section: Discussionmentioning
confidence: 99%